Purchase Decisions Impacted by Service Quality, Price, and Location: A Study on Zakiah Hijab Solution Stores.: Keputusan Pembelian Dipengaruhi oleh Kualitas Layanan, Harga, dan Lokasi: Studi pada Toko Zakiah Hijab Solution. - Agung Indra Lesmana; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2022)
This research aimed to investigate the influence of service quality, price, and location on purchase decisions at Zakiah Hijab Solution Stores in Mojokerto City. The study employed the slovin sampling method, with a sample size of 100 respondents. Primary data was collected and analyzed using Multiple Linear Regression in SPSS 23. The findings revealed that service quality significantly affected purchase decisions, indicating the importance of providing excellent customer service. Additionally, price was found to be a significant factor influencing purchase decisions, highlighting the significance of pricing strategies. Moreover, location emerged as a significant determinant of purchase decisions, emphasizing the importance of store accessibility. Furthermore, the combined effect of service quality, price, and location was found to significantly impact purchase decisions. These results contribute to the understanding of consumer behavior in the hijab retail industry and hold implications for marketing strategies, aiding businesses in enhancing their competitiveness and attracting a larger customer base. Highlights: Service quality significantly influences purchase decisions: The study demonstrates the crucial role of providing excellent service quality in shaping customers' purchasing behavior at Zakiah Hijab Solution Stores. Price is a determining factor in purchase decisions: The research highlights the impact of pricing strategies on customers' decision-making process, emphasizing the significance of competitive pricing. Location plays a vital role in purchase decisions: The findings underscore the importance of store location and accessibility as key factors influencing customers' choices when shopping at Zakiah Hijab Solution Stores. Keywords: Service quality, Price, Location, Purchase decisions, Zakiah Hijab Solution Stores